Important Aspects of Personal Development In High Schools - Nigora Akbarovna Sharopova; Ruhshona Quvonova (Euro Asian Journal Publishing, 2024)
The article talks about the important aspects of personality development in secondary schools.
Keywords: Personality; creativity; talent; improvement